2019
DOI: 10.1177/0973258619876222
|View full text |Cite
|
Sign up to set email alerts
|

Stealing Thunder in Negative Political Advertising: The Persuasive Impact of One-sided and Two-sided Negative Messages on Partisan Individuals

Abstract: Although two-sided persuasion is a common technique in political speeches, few research has reported the relative persuasiveness of a one-versus two-sided message in the context of negative political advertising. Participants ( N = 116) viewed a negative political ad, varying in message sidedness (one-sided vs. two-sided) and partisan match (partisan-match vs. partisan-mismatch vs. unaffiliated). Multivariate results revealed the relative advantage of two-sided persuasion in the partisan-match condition where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…In contrast, one-sided messages only provide positive information (Crowley and Hoyer 1994). Whether two-sided messages are effective, the debate is still unresolved and ongoing (Eisend 2013;Küster and Eisend 2016;Pizzutti et al 2016;Huertas and Hanna 2020;Cornelis et al 2020;Kim 2020). Although various explanations have been offered for the discrepancy in empirical findings, such as methodological differences (e.g., Crowley and Hoyer 1994;Eisend 2006) or absence of a specific theory within the context of marketing information processing (e.g., Crowley and Hoyer 1994), past research has not studied the possibility that such differences may stem from core cultural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, one-sided messages only provide positive information (Crowley and Hoyer 1994). Whether two-sided messages are effective, the debate is still unresolved and ongoing (Eisend 2013;Küster and Eisend 2016;Pizzutti et al 2016;Huertas and Hanna 2020;Cornelis et al 2020;Kim 2020). Although various explanations have been offered for the discrepancy in empirical findings, such as methodological differences (e.g., Crowley and Hoyer 1994;Eisend 2006) or absence of a specific theory within the context of marketing information processing (e.g., Crowley and Hoyer 1994), past research has not studied the possibility that such differences may stem from core cultural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that these effects hold for new forms of advertising, such as native ads, social media ads, and digital influencer merchandising (De Veirman & Hudders, 2020; Krouwer et al, 2021; Lee & Johnson, 2022). Outside the advertising field, two‐sided refutational messages have been shown to lead people with strongly held beliefs to be more open to counter attitudinal information on issues as diverse as gun control (Xu & Petty, 2021), vaccination (Featherstone & Zhang, 2020), genetically modified crops (Lyons et al, 2019), and political candidates (Kim, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given that political advertising has been extensively regarded as an effective persuasive technique with a variety of optimistic effects on voters’ attitudes, political leaders have therefore used it as a potent medium to package their images, as well as to reach voters effectively. Conversely, scholars have also identified that persuasion is not a straightforward process and can be affected by message frames (Han et al, 2018), message tone (advocacy or attack) (Halle, 2017), two-sided persuasion (Kim, 2020) and personal traits (Tory Higgins et al, 2003). In this respect, the content of political advertisements interact with other influential factors such as personality traits or values and, consequently, trigger either promotion- or prevention-oriented apprehensions.…”
Section: Introductionmentioning
confidence: 99%